A New Experimental Approach to Evaluate Plasma-induced Damage in Microcantilever - Nishimori, Yuki; Ueki, Shinji; Sugiyama, Masakazu; Samukawa, Seiji; Hashiguchi, Gen (UI Scholars Hub, 2013)
Plasma etching, during micro-fabrication processing is indispensable for fabricating MEMS structures. During the plasma processes, two major matters, charged ions and vacuum–ultraviolet (VUV) irradiation damage, take charge of reliability degradation. The charged ions induce unwanted sidewall etching, generally called as “notching”, which causes degradation in brittle strength. Furthermore, the VUV irradiation gives rise to crystal defects on the etching surface. To overcome the problem, neutral beam etching (NBE), which use neutral particles without the VUV irradiation, has been developed. In order to evaluate the effect of the NBE quantitatively, we measured the resonance property of a micro-cantilever before and after NBE treatment. The thickness of damage layer (δ) times the imaginary part of the complex Young's modulus (Eds) were then compared, which is a parameter of surface damage. Although plasma processes make the initial surface of cantilevers damaged during their fabrication, the removal of that damage by NBE was confirmed as the reduction in δEds. NBE will realize a damage-free surface for microstructures.